The development of badminton blow basic exercise model in early age 10-11 years (through exercise drill approach) - Anggriawan, Hariyuda; Doewes, Muchsin; Purnama, Sapta Kunta (Journal of Education, Health and Sport, 2018)
Background: The purpose of this study was to determine and analyze (1) the effect of developing a model of training on basic exercise of badminton in children aged 10-11 years (through drill exercise approach) (2) comparing the effectiveness level of the original conventional training with the development of technical training models Badminton Basics for Early Childhood 10-11 Years (Through Drill Practice Approach) (3) creating products in the form of training models for basic Badminton in Early Childhood 10-11 Years Old (Through Drill Practice Approach Subjects and Methods: This study uses the Model Development method. The data obtained in this study are qualitative data and quantitative data. The population is PB Putra Utama Sukoharjo members aged 10-11 years in the early age category, amounting to 12 people and divided into 2 groups, namely the trial group and the control group respectively. the number of 6 children. Results: Based on expert validation and group trials. Experts and experts assess the aspects of material quality and content aspects with an average of 87.2% including valid categories to be used, while badminton experts and experts assess the aspect of appearance and effectiveness aspects with a mean score of 90.02% including valid categories for use. Assessment of coaches/trainers through small group trials a percentage of 85.76% valid categories for use. The results of large group trials, based on the aspect of appearance, content aspects, and aspects of the training program, obtained an average score of 80.79% including valid categories for use. 4) The average increase in the trial group (59.06%) was higher than the control group (44.482%). 5) This product is declared valid and effective. Conclusion: The conclusions of this study are (1) Development of the basic exercise model of badminton punch on early childhood aged 10-11 years (through drill training approach) influences the significant increase in mastery of basic punch techniques, (2) Development of basic technical training models Badminton punches in early childhood aged 10-11 years (through drill training approach) are more effective than conventional models or exercises (3) products in the form of exercise models for basic badminton in children aged 10-11 years (through drill practice approach) are good books and video tutorials become an exercise model that is suitable for the growth and development of early childhood 10-11 years effective and easy to understand as a guide in applying the exercise model.